Studies on seminal attributes of Patanwadi rams during breeding and non-breeding seasons - NEMA, S P; KAVANI, F S; GAJBHIYE, P U (The Indian Journal of Animal Reproduction, 2023)
Semen ejaculates (90) collected in artificial vagina from 5 mature Patanwadi rams covering breeding andnon-breeding seasons (one year) were evaluated for the biophysical attributes. The overall means of variou;seminal attributes observed were: ejaculate volume 0.91±0.11 ml, mass activityJ.80±0.~9, pH 6.97±0.02, spermconcentration 2730.44±50.50 million/ml, live sperm count 88.49±0.54 %, morphologieally abnormal sperms5.93±0.12 % and abnormal acrosome score 4.57±0.13 %. ·Variation between rams was highly significant (P
Keywords: Patanwadi ram; Season; Seminal attributes; lnterrefationships